Search
Ask a question
0

(-3 w^2)^3 / v^4

 

Simplify

(-3 w^2)^3 / v^4

(v^-2)^3

8 b^5 ( 4 - 10 b^2 )

 

 

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Kenneth W. | Algebra to calculus, chemistry, music, and more!Algebra to calculus, chemistry, music, a...
4.5 4.5 (46 lesson ratings) (46)
0

These all use the power rule property of (m^n)a = ma*n.  For instance, (w2)3 = w2*3 = w6.  This works because w2 is the same as (w * w). 

(w2)3 = (w2 * w2 * w2) = [(w * w) * (w * w) * (w * w)] = w6.

Go ahead and apply this template to your other problems.  It should help you connect the dots from there.